Mammals show no spatiotemporal avoidance of trails or roads in a forested raptor sanctuary - Keller, Shannon M.; Mashintonio, Andrew F.; Barber, David R. (Frontiers in Ecology and Evolution, 2025)
Disturbance from human presence can cause changes in wildlife behavior, physiology, and fitness. Wildlife in conservation areas that also serve as recreational areas for people are especially vulnerable to these disturbances. Animals may avoid human presence spatially, by moving to new locations, or temporally, by becoming more active when human activity is low. We examined spatial and temporal changes to mammal occupancy (interpreted as site use) and detection probability at Hawk Mountain Sanctuary (HMS), a raptor sanctuary that provides both wildlife conservation and hiking trails. We placed 12 camera traps at random locations throughout the sanctuary and nearby Acopian Center, capturing images from March to November 2022. We used the distances to trails and roads as covariates representing human presence, time of day (dawn, day, dusk, or night) to estimate temporal response, and distance to streams and elevation as environmental covariates that can affect site use. Fifteen mammal species were detected over 2,837 trap nights. Bobcat (Lynx rufus) were the only species to show potential spatial avoidance of humans by avoiding roads, while no species showed temporal avoidance. Time of day affected detection probability for most species but aligned with each species’ expected diel patterns. These results suggest that mammals at HMS are not shifting their behavior to avoid trails and roads. Despite the potential for human-wildlife conflict in a multiple-use conservation area, this study demonstrates that managers can be successful at balancing recreational opportunities for people with maintenance of diverse wildlife.